Incidence of Coronary Obstruction During Aortic Valve Implantation: Meta-Analysis and Mixt-Treatment Comparison of Self-Expandable Versus Balloon-Expandable Valve Prostheses - Yu Fei Wang; Zai Qiang Liu; Xiao Teng Ma; Li Xia Yang; Zhi Jian Wang; Yu Jie Zhou (Reviews in Cardiovascular Medicine)
Background: Recently, the transcatheter aortic valve replacement (TAVR) indications have expanded; meanwhile, valve systems have continuously evolved and improved. However, coronary occlusion (CO), a rare but catastrophic consequence of TAVR surgery, limits the expansion of indications for TAVR. Moreover, comparisons between different systems remain scarce. This study aimed to evaluate the incidence of CO associated with TAVR, specifically comparing self-expanding valves (SEVs) and balloon-expandable valves (BEVs), and further assess the safety profile of these valve subtypes. Methods: The primary outcome of interest was the incidence of CO during TAVR using BEVs or SEVs. Electronic databases were searched from January 2009 to June 2023, and this study included randomized controlled trials, observational studies, and propensity pair-matched studies. Heterogeneity and inter-study variance were assessed using Cochran’s Q, I2, and τ2 (Sidik–Jonkman estimator). Random effects models were used based on the Bayesian theory framework. The node-splitting approach was generated to determine study network inconsistency. The convergence of the model was evaluated using the trajectory map, density map, and the potential scale reduction factor (PSRF). Rank sort graphs illustrate the best valve deployment techniques or valve types. Results: A total of 830 articles were searched referring to the incidence of CO using the valve deployment system of SEVs or BEVs during the TAVR procedure, from which 51 were included (27,784 patients). The procedure incidence of coronary obstruction was 0.4% for the SEVs and 0.6% for the BEVs. Treatment ranking based on network analysis revealed SAPIEN 3 (Edwards Lifesciences (Irvine, CA, USA)) possessed the best procedural CO incidence (0.05%) performance, whereas SAPIEN (Edwards Lifesciences (Irvine, CA, USA)) produced the worst (1.04%). Conclusions: Our study indicates that CO incidence was not reduced during TAVR with BEVs compared to SEVs. SAPIEN 3 and SAPIEN had the lowest and highest TAVR-associated CO rates, respectively. These findings suggest that the SAPIEN 3 valve may be the best choice for reducing CO risk, and future studies should focus on its applicability in different populations. More randomized controlled trials with head-to-head comparisons of SEVs and BEVs are needed to address this open question. The PROSPERO registration: CRD42024528269, https://www.crd.york.ac.uk/PROSPERO/view/CRD42024528269.